Karakteristik Pembakaran Biobriket Kulit dan Cangkang Karet (Hevea Brasiliensis) dengan Perekat Glyserin - Mariki, I Wayan Wawan; Wahyudi, Slamet; Widhiyanuriyawan, Denny (Rekayasa Mesin, 2017)
Some studies have been done on utilizing biomass from agriculture such as the leather and shell of rubber (Hevea brasiliensis) were not used optimally in Indonesia as an alternative energy which developed by making biobriquet to achieved the higher energy that could be used in the combustion process. In this study, the biobriquet was made of the leather and the shell of rubber by comparisson of the leather and shell were: 0%: 91%; 45.5%: 45.5%; 55%: 36%; 64%: 27%; 91%: 0%.Glyserin 9% for each percentage of biobriquet was used as adhesive material and the drying temperature of 110 C. This study aims to investigate the characteristics of biobriquet combustion which made of the leather and shell of rubber. The results shows that the biobriquet combustion process which made of 64% rubber leather and 27% rubber shell has a calorific value of 5313,923 Kal/gr. In 20 seconds of initial ignition, the combustion process shows the improvement such as increased concentrations of the flammable leather, bluish red fire.